A Review of Modern Approaches of Digitalization in Oil and Gas Industry - Al-Rbeawi, Salam (Upstream Oil and Gas Technology, 2023)
This paper introduces a review of the modern approaches of digitalization in the oil and gas industry. The objective is understanding the current applications of the traditional technologies used in the petroleum industry and studying the opportunities for implementing innovative digital tools and systems that could enhance the operational efficiency and reduce the cost, risk, and environmental impacts. The paper consists of several tasks starting from reviewing the present technologies used mainly in the upstream activities: exploration, field development, drilling and completion, and operation and production. The techniques used for gathering and analyzing the big data packages received from unlimited digitalized resources is the second task covered in this paper while the computing technologies such as cloud and cognitive computing as well as the advanced analytical and numerical solutions developed by real-time algorithms is the third task. Detail information about the short- and long-term digitalization technologies in both hardware and software parts is represented in this paper such as robotics and automation, powerful sensors and measuring tools, unmanned vehicles and drones, 3D printers and wearable gadgets as well as artificial inelegance, machine learning, and digital-twin computing. Real examples of currently used digitalized applications in different upstream sections of the petroleum industry are demonstrated while the expected added values created by the digitalization for the industry and communities and the possible changes either positively or negatively in the operational costs, maintenance patterns, workforce safety, environmental impacts, job positions, and the required skills and experiences during digitalization era are explained. The outcomes are summarized in the following points. The digitalization should be the priority for most upstream companies in order to enhance and optimize the production system. The big volume of data may require innovative computing tools that could develop powerful analytical models used for calibrating the production environment and maximizing the production capacity of oil and gas fields. Data transfer and data sharing are two key factors in the digital transformation where the integrated data platforms could enhance the collaboration among the participants of the oil and gas ecosystems and accelerate innovative solutions. The digital era may lead to a sharp decline in the workforce and significant changes in the job position description as the human intervention with the production system might be minimized. The expected added value of the digital transformation during the next decades will be very big wherein the upstream petroleum industry may have the biggest share that could be more than 60% of the total investments while the midstream industry may have only 10%. There will be also a lot of challenges represented by the fact that the petroleum industry has not yet made the necessary shift in mindset to embrace the digitalization potential. Moreover, the digitalization era may require new revolutionized regulations especially in terms of sharing the data and changing the structures of the organizations as well as the workforces.